2021
DOI: 10.3390/pharmaceutics13060901
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Gold Nanoparticles in the Anterior Chamber of the Eye after Intracameral Injection for Glaucoma Therapy

Abstract: In glaucoma therapy, nanoparticles (NPs) are a favorable tool for delivering drugs to the outflow tissues of the anterior chamber of the eye where disease development and progression take place. In this context, a prerequisite is an efficient enrichment of NPs in the trabecular meshwork with minimal accumulation in off-target tissues such as the cornea, lens, iris and ciliary body. We evaluated the optimal size for targeting the trabecular meshwork by using gold NPs of 5, 60, 80 and 120 nm with a bare surface … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…For this reason, the ocular tolerability of the nanoparticle formulation should be taken into consideration before in vivo application. Fibroblasts served as a disease model for glaucomatous cells due to the fact that cells in the trabecular meshwork increasingly acquire the phenotype of contractile myofibroblasts during glaucoma development (Sonntag et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the ocular tolerability of the nanoparticle formulation should be taken into consideration before in vivo application. Fibroblasts served as a disease model for glaucomatous cells due to the fact that cells in the trabecular meshwork increasingly acquire the phenotype of contractile myofibroblasts during glaucoma development (Sonntag et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Apaolaza et al [ 55 ] immobilized low molecular weight HA (5 kDa) on the surface of GNPs and visually observed that HA passivation promoted enhanced particle distribution across the vitreous matrix and ocular tissues after local injection in ex vivo porcine eyes. Sonntag et al [ 56 ] also conjugated thiolated HA to GNPs of various sizes (5, 60, 80, and 120 nm) and quantified their distribution in the anterior chamber of the eye in an ex vivo porcine model. The authors found that the HA coating prevented aggregation of NPs inside the trabecular meshwork and yielded reduced gold content in off-target tissues in the anterior eye, such as the cornea, lens, iris, and ciliary body.…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of ophthalmic formulations available on the market are in the form of eye drops or ointments, indicating that topical administration is the preferred means of administration. According to a recent survey, the global ocular drug technology market was valued at $29.2 billion in 2016, and it is predicted to grow to $42.7 billion by 2023 [4]. Intraocular pressure (IOP) is a key risk factor for the disease, and eye drops are the first-line treatment for lowering it when it becomes elevated.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%